Passive compliance or active innovation: The diffusion of public sport policies in China - Zhiliang Li; Jian Liu; Hailin Lu; Jingjing Zhou (PLoS ONE, 2025)
As an important tool for governing, regulating, and safeguarding national sports, sports policy not only centralizes and expresses the state’s vision for sports but also advances the development of the sports economy, and distributes the benefits of social sports. Accordingly, we collect policy samples from 31 provinces of China. Adopting the central–local relationship perspective, we use the grey correlation analysis method to explore the intrinsic relationship between the factors influencing the diffusion of public sports policies and the degree of policy text reproduction by provincial governments. We aim to encourage provincial governments to innovate policy texts based on local development needs, geographic position, and resource capabilities, This will enhance the diffusion of public sports policies and contribute to national and global sports governance. The diffusion of China’s public sports policies is influenced by six secondary indicators: economic level, population size, sports organizations, public sports demand, central government policy pressure, and learning effect. The policy environment, shaped primarily by central government policy pressure and the learning effect, has the greatest influence on the reproduction of provincial public sports policy texts.